Identification of cholesterol binding sites in the serotonin(1A) receptor - Sengupta, Durba; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2012)
The serotonin(1A) receptor is a representative member of the G protein-coupled receptor (GPCR) superfamily and serves as an important drug target in the development of therapeutic agents for neuropsychiatric disorders. Previous work has shown the requirement of membrane cholesterol in the organization, dynamics, and function of the serotonin(1A) receptor. We show here that membrane cholesterol binds preferentially to certain sites on the serotonin(1A) receptor by performing multiple, long time scale MARTINI coarse-grain molecular dynamics simulations. Interestingly, our results identify the highly conserved cholesterol recognition/interaction amino acid consensus (CRAC) motif on transmembrane helix V as one of the sites with high cholesterol occupancy, thereby confirming its role as a putative cholesterol binding motif. These results represent the first direct evidence for membrane cholesterol binding to specific sites on the serotonin(1A) receptor and represent an important step in our overall understanding of GPCR function in health and disease.

Increased cholesterol interactions in the active conformational state of the glucagon-like peptide-1 receptor - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2026)
The glucagon-like peptide-1 receptor (GLP-1R) is a class B G-protein-coupled receptor that plays an important role in metabolic regulation and consequently is a target for type 2 diabetes and obesity therapeutics. Although cholesterol has been reported to be implicated in receptor activation, its interactions with the receptor during the activation cycle have not been probed. Using coarse-grained molecular dynamics simulations, we have characterized the cholesterol interactions with GLP-1R in four conformational states: the inactive, partially active, GLP-1-bound active, and exenatide-bound active conformational states. We observed that the cholesterol hotspots vary between the receptor states with an increased enrichment of cholesterol around the receptor in the active conformational states. Importantly, more favorable interaction energetics and increased residence times of cholesterol were identified in the active conformational state of the receptor, although lower in magnitude than previously reported. Notably, subtle differences could be distinguished between the GLP-1-bound and exenatide-bound receptor, underlining the ligand-specific effects. Our findings emphasize the increased selectivity of cholesterol toward the active state of GLP-1R and highlight the role of conformational dynamics in receptor-lipid interplay. Our work helps to understand how cholesterol modulates GLP-1R, with potential effects on its role as a regulator in lipid metabolism, thereby opening avenues to leverage these lipid interactions in targeted drug therapy. SIGNIFICANCE This study provides an understanding of how cholesterol directly influences the function of GLP-1R, a key therapeutic target for metabolic diseases including type 2 diabetes and obesity. Using coarse-grained molecular dynamics simulations, we show that cholesterol binding, favorable interactions, and residence times increase when GLP-1R is in its active states. These interactions vary subtly depending on the activating ligand, highlighting ligand-specific effects. Our findings highlight the critical role of conformational dynamics in receptor-lipid interplay and suggest that understanding these cholesterol-GLP-1R interactions could pave the way for novel strategies in targeted drug therapy for metabolic disorders.